The Power of goals : how to achieve outstanding success - Valentine, James Lee (Mandaluyong City, Philippines : National Book Store, 2000)
Goals are the road maps that guide you along your journey of life and show you what is attainable. They are dreams that have become energized through the application of action.
1. choose magnificent goals -- 2. your values define who you are -- 3. how to establish dynamics goals -- 4. set phenomenal goals for your life -- 5.your pure power declaration.
Keywords: GOAL SETTING